Molecular and functional properties of synaptically activated NMDA receptors in neonatal motoneurons in rat spinal cord slices - Abdrachmanova, G; Teisinger, J; Vlachová, V; Vyklický, L (The European journal of neuroscience, 2000)
The functional properties of N-methyl-D-aspartate (NMDA) receptor-mediated excitatory postsynaptic currents (EPSC) were studied in fluorescence-labelled motoneurons in thin spinal cord slices. The deactivation of NMDA receptor EPSCs in motoneurons voltage-clamped at +40 mV was independent of intensity or location of stimulation and of postnatal age [taufast = 28.5 +/- 4.6 ms (63.6 +/- 8.8%) and tauslow = 165.6 +/- 49.6 ms]. In the presence of 1 mM Mg2+ the amplitude of NMDA receptor EPSCs was voltage-dependent. Boltzmann analysis of the relationship between peak NMDA receptor EPSC amplitude and membrane potential suggested an apparent Kd of Mg2+ (at 0 mV) of 0.87 mM. Nonstationary variance analysis of NMDA receptor EPSCs gave an estimated single-channel conductance of 59 +/- 14 pS. Direct measurement of the NMDA receptor channel openings in outside-out patches isolated from motoneurons indicated the presence of single-channel conductance levels of 21.8 +/- 2.8 pS, 37. 1 +/- 3.2 pS, 49.6 +/- 5.1 pS and 69.6 +/- 4.2 pS. Single-cell RT-PCR analysis of mRNA revealed that NR1, NR2A-D and NR3A transcripts were expressed in motoneurons. These results suggest that specific assembly of NMDA receptor subunits in motoneurons determines the functional and pharmacological properties of the receptors in these cells.
Keywords: Electrophysiology; mícha; membránové potenciály; Excitatory Postsynaptic Potentials; Synapses; motorické neurony; Excitatory Amino Acid Antagonists; Animals, Newborn; Membrane Potentials; krysa rodu Rattus; In Vitro Techniques; synapse; elektrická stimulace; techniky in vitro; Reverse Transcriptase Polymerase Chain Reaction; hořčík; Electric Stimulation; Patch-Clamp Techniques; 6-kyano-7-nitrochinoxalin-2,3-dion; receptory N-methyl-D-aspartátu; excitační postsynaptické potenciály; metoda terčíkového zámku; antagonisté excitačních aminokyselin; Motor Neurons; novorozená zvířata; polymerázová řetězová reakce s reverzní transkripcí; Spinal Cord; zvířata; elektrofyziologie; 6-Cyano-7-nitroquinoxaline-2,3-dione; Rats; Receptors, N-Methyl-D-Aspartate; Animals; Magnesium